Design and Build Mppt Solar Charge Controller Using Buck Converter On Photovoltaic Based Microcontroller Pic - Widodo, Teguh Rahayu; Fatkhurrozi, Bagus; Setiawan, Hery Teguh (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
Photovoltaic (PV) is a component for converting solar energy into electrical energy. On the other hand, the characteristics of PV performance are fluctuating, additional circuits are needed to maximize PV performance. This research discusses the maximum power point tracker (MPPT) in a solar charge controller system using PIC microcontroller as a solution to maximize PV performance. The MPPT algorithm used is perturb and observe (PO) with PV power parameters because this algorithm is often used and has good efficiency. This research system was tested using a voltage scale of 15 V, 16V, 17 V, 18.1 V, 19 V, 20 V, 21 V, 22 V, 23.1 V, 24.1 V, and 25 V with the lowest average error value of 3.01447379% and highest 4.312288%. Testing the working characteristics of the 120WP solar panel shows that the solar panel will work optimally when the conditions are sunny and the temperature is not high. The results of testing solar panels with the highest average output voltage of 22.1 V. From testing the system on solar panels shows the value of the ADC output voltage with an average of 12.603V in sunny conditions, 12.372V in sunny cloudy conditions, 12.23V in cloudy conditions, 12.5 V in an obstructed condition. In testing system efficiency using the PO algorithm with an average result of 80.4818%.